2021
DOI: 10.1093/qjmed/hcab100.082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intradialytic exercise on the inflammatory markers in prevalent hemodialysis patients

Abstract: Background Chronic low-grade inflammation is a feature of chronic kidney disease associated with increased risk of multiple morbidities and mortalities. Dialysis patients lead a sedentary life style which could add to this risk. Aim assessment of the effect of intradialytic exercise IDE on inflammatory markers in prevalent hemodialysis HD patients. Patients and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Pharmacologic strategies, although largely lacking in clinical outcomes, include IL-1 inhibitors, statins, cholecalciferol, angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEi/ARB), sevelamer [50]. In a prospective study, Elshinnawy et al found that intradialytic exercise not only decreased the levels of the inflammatory markers, CRP and IL-6, but also increased serum albumin levels [51].Other non-pharmacologic strategies include dietary factors and short, daily dialysis, but data is still lacking in this area [50].…”
Section: Preventionmentioning
confidence: 99%
“…Pharmacologic strategies, although largely lacking in clinical outcomes, include IL-1 inhibitors, statins, cholecalciferol, angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEi/ARB), sevelamer [50]. In a prospective study, Elshinnawy et al found that intradialytic exercise not only decreased the levels of the inflammatory markers, CRP and IL-6, but also increased serum albumin levels [51].Other non-pharmacologic strategies include dietary factors and short, daily dialysis, but data is still lacking in this area [50].…”
Section: Preventionmentioning
confidence: 99%